Racial Disparities in Invasive Management for Patients With Acute Myocardial Infarction With Chronic Kidney Disease. (January 2022) - Rymer, Jennifer A.; Li, Shuang; Pun, Patrick H.; Thomas, Laine; Wang, Tracy Y.
Abstract : Background: Due to increased risks of contrast nephropathy, chronic kidney disease (CKD) can deter consideration of invasive management for patients with myocardial infarction (MI). Black patients have a higher prevalence of CKD. Whether racial disparities exist in the use of invasive MI management for patients with CKD presenting with MI is unknown. Methods: We examined 717 012 White and 99 882 Black patients with MI treated from 2008 to 2017 at 914 hospitals in the National Cardiovascular Data Registry Chest Pain—MI Registry. CKD status was defined as estimated glomerular filtration rate (eGFR) ≥90 mL/(min·1.73 m 2 ; no CKD), eGFR <90 but ≥60 (mild), eGFR <60 but ≥30 (moderate), and eGFR <30 or dialysis (severe). We used multivariable logistic regression models to examine the interaction of race and CKD severity in invasive MI management. Results: Among those with MI, Black patients were more likely than White patients to have CKD (eGFR <90; 61.4% versus 58.5%; P <0.001). Among those with MI and CKD, Black patients were more likely than White patients to have severe CKD (21.2% versus 12.4%; P <0.001). Patients with CKD were more likely than those without CKD to have diabetes or heart failure; Black patients with CKD were more likely to have these comorbidities when compared with White patients with CKD (all P <0.0001). Black race and CKD were associated with a lower likelihood of invasive management (adjusted odds ratio, 0.78 [95% CI, 0.75–0.81]; adjusted odds ratio, 0.72 [95% CI, 0.70–0.74]; P <0.001 for both). At eGFR levels ≥10, Black patients were significantly less likely than White patients to undergo invasive management. Conclusions: Black patients with MI and mild or moderate CKD were less likely to undergo invasive management compared with White patients with similar CKD severity. National efforts are needed to address racial disparities that may remain in the invasive management of MI. Abstract : Supplemental Digital Content is available in the text.